2006
DOI: 10.1111/j.1365-2788.2006.00824.x
|View full text |Cite
|
Sign up to set email alerts
|

Improving the health of people with intellectual disabilities: outcomes of a health screening programme after 1 year

Abstract: This is the first study to demonstrate sustained benefits in health outcomes from a clinical intervention for adults with IDs compared with standard treatment alone. Its routine implementation is feasible, and would reduce health inequalities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
119
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 96 publications
(129 citation statements)
references
References 31 publications
8
119
0
2
Order By: Relevance
“…The intervention was less effective than the previous Scottish intervention study, 18 in which health checks were undertaken by intellectual disabilities nurses rather than practice nurses, and took about five times longer. The follow-up duration was also longer in that study (1 year) compared with our study (9 months).…”
Section: Discussionmentioning
confidence: 65%
See 4 more Smart Citations
“…The intervention was less effective than the previous Scottish intervention study, 18 in which health checks were undertaken by intellectual disabilities nurses rather than practice nurses, and took about five times longer. The follow-up duration was also longer in that study (1 year) compared with our study (9 months).…”
Section: Discussionmentioning
confidence: 65%
“…For 90% power and 5% significance, the previous Scottish intervention study 18 showed that 51 participants would be needed in each group to detect a rise in the proportion of new health needs being met, from a third to two-thirds (nQuery Advisor v 4.0, based on a continuity-corrected χ 2 test); or 64 in each study group allowing for 20% attrition. The amount of inflation in sample size needed because of the cluster-randomised design depends on the average cluster size (expected to be 2.5 in this investigation) and intraclass correlation coefficient (ICC).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations